2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM) 2016
DOI: 10.1109/speedam.2016.7525826
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of a doubly-salient motor with multi-V-shape ferrite magnets

Abstract: International audienceThis paper presents the analysis of a novel doubly salient structure with concentrated tooth winding and multi-V shape ferrite magnets. Permanent Magnet Synchronous Machines (PMSM) have been universally used with rare-earth magnets or with ferrite magnets and distributed winding. The proposed topology is presented as an improvement to PMSM for high torque and low-speed applications. It has low copper losses due to its short end-winding and benefits from a low cost by virtue of its lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The discrepancy is below 2% [14]. The 18/16 structure allows the development of a smooth torque [6]. Thus, the calculation of the torque ripple is not included in the AM.…”
Section: E Finite Element Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy is below 2% [14]. The 18/16 structure allows the development of a smooth torque [6]. Thus, the calculation of the torque ripple is not included in the AM.…”
Section: E Finite Element Validationmentioning
confidence: 99%
“…The previously studied structures were generally designed with conventional distributed winding. However, novel doubly salient topologies with multi-V shape interior permanent magnets and concentrated tooth winding were recently studied and the results showed that they are capable of developing a high torque at low rotational speed [6]. Besides, the concentrated Paul winding reduces the length of the end-winding which decreases the copper losses and may improve the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The average torque (Tavg), the internal power factor (PFint) and the internal voltage (Vint) are calculated at 4 static positions for an accurate estimation [7]. They are expressed by (4), (5) and (6) respectively.…”
Section: = ( ) +mentioning
confidence: 99%
“…Non-rareearth permanent magnets such as ferrite were used as an additional torque source in synchronous reluctance motors [4], [5]. The previously mentioned structures are generally designed with distributed winding but more novel topologies with multi-V shape interior permanent magnets and concentrated tooth winding were also capable of developing a high torque at low rotational speed [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation